Serum from Adolescents with High Polyphenol Intake Exhibits Improved Lipid Profile and Prevents Lipid Accumulation in HepG2 Human Liver Cells. (13th February 2023) - Augimeri, Giuseppina; Avolio, Ennio; Caparello, Giovanna; Galluccio, Angelo; De Rose, Daniela; Vivacqua, Adele; Morelli, Catia; Barone, Ines; Catalano, Stefania; Andò, Sebastiano; Giordano, Cinzia; Sisci, Diego; et al.
Abstract : The traditional Mediterranean diet (MD) is characterized by a high phenolic-rich food intake, including in particular vegetables and fruits, but also legumes, whole grain cereals, nuts, and extra virgin olive oil. Evidence for beneficial effects of polyphenols in humans depends on the amount consumed and on their bioavailability. Here, we evaluated the association between the estimated polyphenol intake by fruits and vegetables food source and serum biochemical parameters in healthy adolescents, recruited into the DIMENU research project. Categorizing adolescents into three groups according to their estimated total polyphenol intake, we found that adolescents who declared high consumption of polyphenols had a higher adherence to the MD and had a better serum lipid profile than adolescents consuming low amounts of polyphenols. Moreover, using human HepG2 liver cells treated with oleic acid as an in vitro model for studying lipid accumulation, we showed that intracellular lipid accumulation is alleviated by serum from adolescents consuming a polyphenol-rich diet following MD recommendations. Our data underline the importance of promoting adherence to the typical MD foods as a superior strategy to prevent metabolic and chronic diseases and to ensure a better quality of life among adolescents.